Ground Penetrating Radar as a Tool for the Diagnostics of Concrete Pavements - Stryk, J.; Matula, R. (Transactions on Transport Sciences, 2009)
This paper describes the basic possibilities for the usage of ground penetrating radar (GPR) in road diagnostics. The opportunity for multi-channel GPR use and the limitations arising from measurements performed at high speeds are described. Particular attention is paid to the problems of the diagnostics of concrete pavements. The radar configuration used for location of dowel bars and tie bars is presented.
Keywords: Ground penetrating radar; GPR; diagnostics; pavement; guidelines.